Design and Characterization of a Novel Hapten and Preparation of Monoclonal Antibody for Detecting Atrazine - Lingyuan Xu; A.M. Abd El-Aty; Jae-Han Shim; Jong-Bang Eun; Xingmei Lei; Jing Zhao; Xiuyuan Zhang; Xueyan Cui; Yongxin She; Fen Jin; Lufei Zheng; Jing Wang; et al. (Foods, 2022)
This study provides the first design and synthetic protocol for preparing highly sensitive and specific atrazine (ATR) monoclonal antibodies (mAbs). In this work, a previously unreported hapten, 2-chloro-4-ethylamino-6-isopropylamino-1,3,5-triazine, was designed and synthesized, which maximally exposed the characteristic amino group ATR to an animal immune system to induce the expected antibody. The molecular weight of the ATR hapten was 259.69 Da, and its purity was 97.8%. The properties of the anti-ATR mAb were systematically characterized. One 9F5 mAb, which can detect ATR, was obtained with an IC50 value (the concentration of analyte that produced 50% inhibition of ATR) of 1.678 µg/L for ATR. The molecular weight for the purified 9F5 mAb was approximately 52 kDa for the heavy chain and 15 kDa for the light chain. The anti-ATR mAb prepared in this study was the IgG1 type. The working range of the standard curve (IC20 (the concentration of analyte that produced 20% inhibition of ATR)—IC80 (the concentration of analyte that produced 80% inhibition of ATR)) was 0.384 to 11.565 µg/L. The prepared anti-ATR mAb had high specificity, sensitivity, and affinity with low cross-reactivity. The prepared anti-ATR mAb could provide the core raw material for establishing an ATR immunoassay.